A Lysosome‐Targeting AIEgen for Autophagy Visualization. Issue 4 (20th December 2015) - Leung, Chris Wai Tung; Wang, Zhiming; Zhao, Engui; Hong, Yuning; Chen, Sijie; Kwok, Ryan Tsz Kin; Leung, Anakin Chun Sing; Wen, Rongsen; Li, Bingshi; Lam, Jacky Wing Yip; Tang, Ben Zhong
Abstract : In this work, a morpholine‐functionalized aggregation‐induced emission luminogen (AIEgen), AIE‐LysoY, is reported for lysosomal imaging and autophagy visualization. To attain outstanding imaging contrast, AIE‐LysoY is equipped with excited state intramolecular proton transfer (ESIPT) characteristic. AIE‐LysoY provides a new platform for lysosome visualization with good biocompatibility, large Stokes shift, superior signal‐to‐noise ratio, and high photostability.